Assessment of pheromone specificity in Thaumatotibia leucotreta (Meyrick) populations with focus on pest monitoring and the regional rollout of the sterile insect technique in citrus - Joubert, Francois D (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2018)
False codling moth (FCM), Thaumatotibia leucotreta (Meyrick) (Lepidoptera: Tortricidae) is considered the most important indigenous pest of citrus in southern Africa. It is recognized by several markets as a phytosanitary organism and the efficient control of this pest is now more important than ever. The pheromone communication between the male and female moths has been exploited in order to control FCM through the sterile insect technique (SIT). The sterilized males used for all SIT programmes across South Africa come from a colony that originates from wild material collected from the Citrusdal area of the Western Cape Province. The aim of this study was to determine if any differences in attractiveness of females to males exist between different geographical populations of FCM and if so what impact this would have on the male's ability to locate females from other populations via the volatile sex pheromone released by the female. Laboratory trials with Y-tube olfactometers and flight tunnels tested the attraction of male moths to virgin females, but did not yield any consistent results. Field experiments were conducted with sterile male Citrusdal moths released and recaptured in yellow delta traps in two separate trials. For one trial, the traps were baited with live virgin females from five different geographical populations including Addo, Nelspruit, Marble Hall, Citrusdal and the Old colony, which is a mixture of several populations. For the other trial traps were baited with various synthetic pheromone blends including three regional blends which included South Africa, Ivory Coast and Malawi and three commercial blends including Pherolure, Isomate and Checkmate. For the virgin female trial the Citrusdal males showed a significant preference for females from their own population. There was also a significant difference in the recaptures from the different synthetic pheromones. The South African blend was the most attractive of all the regional and commercial blends. A cross-mating trial was also conducted under laboratory conditions in petri dishes with five different FCM populations including Citrusdal, Addo, Marble Hall, Nelspruit and Old (mixed origin). Females produced more eggs when mated with males from the same population for the Addo, Marble Hall, Nelspruit and Old (mixed origin) populations. The only case in which this was statistically significant was for the Marble Hall population. All the crosses produced viable eggs and the origin of the male or female did not influence egg hatch. The results from this study may lead to improvements in both the control and monitoring of FCM populations. The control methods include mating disruption, attract-and-kill and SIT. Tailoring these methods for a specific growing area with a pheromone blend originating from the area or releasing sterile moths from a colony that originates from the area may optimize the available monitoring and control options.
Keywords: Cryptophlebia leucotreta; Pheromone traps; Citrus -- Diseases and pests -- South Africa; Cryptophlebia leucotreta -- Contol; Cryptophlebia leucotreta -- Biological control